Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah - , Setiawan Ario Prabowo, Bernardinus Maria Purwanto D,r., M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine whether the dimensions of service quality that is tangible, reliability, responsiveness, assurance, and emphaty influence on satisfaction and analyze the most dominant factor in influencing customer satisfaction. The population in this study were MC Finance customer. Samples taken 100 respondents Using the Non-Probability sampling with purposive sampling Research results the regression equation as follows: Y = 0.256 X1 + 0.206 X2. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Testing the assumption of classical regression, model contained variables multikolinierity on tangibles, responsiveness and assurance. Influential variable is the variable reliability with regression coefficient 0.256, then emphaty with regression coefficient of 0.206. MC Finance needs to maintain and improve the quality of service that has been assessed both by clients and the need to repair things that are still lacking.